Dimensional change in soft tissues with complete dental prosthesis and its effect on airway space and natural head position - T V Padmanabhan; R Fathima Banu; A Mahalakshmi; Abdul Aziz; Suman Bohra; V Anand Kumar (Wolters Kluwer Medknow Publications, 2015)
Background: Insertion of the intraoral prosthesis causes deflection of the tongue, soft palate affecting the patency of the airway. Aims: To evaluate the cephalometric soft tissue variation in tongue, soft palate, and its effect on posterior airway space in edentulous patients with the insertion of the denture. Settings and Design: Randomized controlled trial. Materials and Methods: Complete denture (CD) prosthesis was fabricated for first time denture wearers comprising 22 males and 18 females within the age range of 50-65 years. Lateral skull radiographs were taken for each of the subjects in their resting position without CDs (T0), with CDs (T1) at least 1-week postinsertion and after 6 months of usage (T2), respectively. The reference points, lines, and angles on the cephalometric films were used to evaluate the position or inclination of the head, variations in tongue position and length, the changes in the anteroposterior dimension of the soft palate, and posterior airway space variations. Intra-investigator error variance was not found to be statistically significant (P < 0.05). Statistical Analysis Used: Using Statistical Package for the Social Sciences (SPSS) v16.0 the significant difference in the paired samples (without CD and with CD) was found using the paired t-test. The probability value P = 0.05 is considered as a significant level. Results : On comparison of T1 and T0, the heads were more extended with the downward position of the tongue with an increase in its length and the posterior airway space was decreased in T1. Significant differences in values were not observed between T1 and T2. Conclusions : With CDs, the change in airway space was related to alteration in soft palate and tongue dimension. There were no changes in dimension at 6 months follow-up.